Evidence of low-energy tunneling excitations in the high-Tc superconductor YBa2Cu3O7-x - Esquinazi, P.; Durán, C.; Fainstein, C.; Nuñez Regueiro, M. (American Physical Society, 1988)
Fil: Esquinazi, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina